Presas sob suspeita:: prognósticos para marfins africanos de exportação - Silva, Renato Araújo da (Afro-Ásia, 2023)
Resenha de: HORTA, José da Silva; ALMEIDA, Carlos; MARK, Peter (orgs.). Marfins africanos no Mundo Atlântico, 1400-1900. Lisboa: Centro de História da Universidade de Lisboa, 2021. 707 p.